Outcome of early cardiopulmonary resuscitation in out-of-hospital cardiac arrest managed in Universiti Kebangsaan Malaysia Medical Centre - Ahmad Khaldun Ismail,; Md Jawi MI,; Mohd Salleh NI,; Hamdan NA,; Shamsuriani Md Jamal,; Shamsul Azhar Shah,; Abdul Razak SN, (Fakulti Perubatan, UKM, 2016)
Out-of-hospital cardiac arrest (OHCA) patients require immediate cardiopulmonary resuscitation (CPR). Early initiation of CPR and defibrillation before arrival at Emergency Department (ED) increases the chance of survival from sudden cardiac arrest. The main objective of this study was to identify the factors that influenced the outcome of early cardiopulmonary resuscitation (CPR) in out-of-hospital cardiac arrest (OHCA) patients managed at the ED of Universiti Kebangsaan Malaysia Medical Centre (UKMMC). The second objective was to determine the incidence of CPR initiated by the public prior to ambulance arrival. The present study was a one-year cross-sectional study. The OHCA patients were identified from the ED resuscitation logbook. Patients’ medical records were used to obtain details of the resuscitation. Factors recorded included: aetiology of arrest, initiation of on-scene CPR, use of automated external defibrillators (AEDs), mode of transportation and the incidence of return of spontaneous circulation (ROSC) in the ED. Categorical data was analysed using chi-square and Fisher exact tests. Nine patients out of 98 had early CPR. Three patients achieved ROSC. Gender was significantly associated with ROSC (p-value=0.015). More patients who received early CPR achieved ROSC compared to those who received late CPR. The provision of early CPR and usage of AEDs by the public is still low. Female gender had a positive influence on ROSC. Efforts are required to increase the awareness and involvement of the public in initiating early CPR prior to the arrival of ambulance service.